THE IMPLEMENTATION OF SOCIAL JUSTICE IN THE INDUSTRIAL RELATION MODEL OF INDONESIA (A LAW PERSPECTIVE ANALYSIS BASED ON INDUSTRIAL RELATION REGULATIONS AND PRACTICE IN INDONESIA) - Gratianus Prikasetya (Problematika Hukum, 2017)
Industrial relation is one of important aspect in daily business practice, but sometimes it become the source of problem in business. The problem often be triggered by a gap between employer and employee interest. Employer business and profit oriented interest sometimes does not meet up with the employees paradigm that commonly work for their survival. The Industrial Relation practice in certain contry is always be related with the industrial relation model that internalised in manpower regulation of certain country. Today‟s there are two types of industrial relation model which commonly used, such as contractualist industrial relation model which relatively consists of individual value and corporatist industrial relation model which usually consist of collectivism value. Each industrial relation model is very dependent with the national public policy. This article will explain the industrial relation model which used and internalised in Indonesia based on the ideology and national identity of Indonesia esepcially social justice value. In regards to explain this article, secondary data such as regulation and theories regarding industrial relation and social justice value that become one of basic principle of Indonesia.